2012
DOI: 10.1590/s2176-94512012000100011
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric deviations present in children and adolescents with temporomandibular joint disorders

Abstract: INTRODUCTION: Temporomandibular disorders (TMD) have proved to be a risk factor for developing hyperdivergent facial growth patterns. OBJECTIVE: The aims of this study were: (1) Assess differences between the cephalometric measurements in children with articular TMD and a control group, before and after mandibular growth peak according to cervical vertebral maturation; and (2) Identify a predictive model capable of differentiating patients with TMD and control group patients based on early cephalometric charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In the five studies from the quantitative synthesis, a total number of 515 subjects were included. Seven studies used the MRI method for disc position classification, whereas just one study used temporomandibular disorders investigation criteria for a diagnosis (RDC/TMD) [ 24 ]. Radiographic evaluation used lateral cephalogram in four studies [ 24 , 25 , 26 , 27 ], and posteroanterior cephalogram in five studies [ 3 , 4 , 26 , 28 , 29 ], Trpkova et al [ 26 ] used both methods.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the five studies from the quantitative synthesis, a total number of 515 subjects were included. Seven studies used the MRI method for disc position classification, whereas just one study used temporomandibular disorders investigation criteria for a diagnosis (RDC/TMD) [ 24 ]. Radiographic evaluation used lateral cephalogram in four studies [ 24 , 25 , 26 , 27 ], and posteroanterior cephalogram in five studies [ 3 , 4 , 26 , 28 , 29 ], Trpkova et al [ 26 ] used both methods.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies used the MRI method for disc position classification, whereas just one study used temporomandibular disorders investigation criteria for a diagnosis (RDC/TMD) [ 24 ]. Radiographic evaluation used lateral cephalogram in four studies [ 24 , 25 , 26 , 27 ], and posteroanterior cephalogram in five studies [ 3 , 4 , 26 , 28 , 29 ], Trpkova et al [ 26 ] used both methods. Bilateral DD was reported in four studies [ 3 , 25 , 26 , 28 ], unilateral DD was reported in [ 3 , 4 , 26 , 28 , 29 ], while two studies did not report the presence of either unilateral or bilateral DD [ 24 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations